Pelatihan Pembuatan Hasil Olahan Jagung Menjadi Susu Jagung Untuk Meningkatkan Pendapatan Ekonomi Warga - Nasrulloh, Muhammad Farid; Fikry, Ulian; Hidayatulloh, Faisol; Nasiruddin, Mohammad; Darmawan, Muhammad Faridl (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Corn (Zea Mays) is one of the world's most important food crops besides wheat and rice. Corn is a type of food that contains carbohydrates which can be used to replace rice. The partners for this activity are in Betek Village, Mojoagung District. Based on the analysis of the situation that emerged, the problems that need to be resolved regarding this activity plan are as follows: (1) There are still many people who do not understand innovations in processed corn products. (2) The need to increase the yield of various types of processed corn and the economy of the Betek Village Community. The objectives of community service activities in the community partnership program through socialization training on processed corn products into corn milk are as follows: (1) To increase innovation from processed corn products. (2) Teach the Betek Village farmer group (KETAN) how to make processed corn products into milk and improve the economy of the Betek Village Community. Based on the results of the questionnaire given: 75% of participants knew about corn milk, and 100% understood how to make corn milk.